2015
DOI: 10.1523/jneurosci.4705-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Automatic and Controlled Semantic Retrieval: TMS Reveals Distinct Contributions of Posterior Middle Temporal Gyrus and Angular Gyrus

Abstract: Semantic retrieval involves both (1) automatic spreading activation between highly related concepts and (2) executive control processes that tailor this activation to suit the current context or goals. Two structures in left temporoparietal cortex, angular gyrus (AG) and posterior middle temporal gyrus (pMTG), are thought to be crucial to semantic retrieval and are often recruited together during semantic tasks; however, they show strikingly different patterns of functional connectivity at rest (coupling with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
158
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(185 citation statements)
references
References 51 publications
23
158
1
3
Order By: Relevance
“…There is considerable evidence demonstrating that these areas are 489 involved in controlled semantic retrieval (e.g. Noonan et al, 2013;Davey et al, 2015), and 490 the present study provides further evidence that this process is independent of modality 491 (Ralph et al, 2017). Interesting in this context is the role of the anterior temporal lobe (ATL).…”
mentioning
confidence: 65%
“…There is considerable evidence demonstrating that these areas are 489 involved in controlled semantic retrieval (e.g. Noonan et al, 2013;Davey et al, 2015), and 490 the present study provides further evidence that this process is independent of modality 491 (Ralph et al, 2017). Interesting in this context is the role of the anterior temporal lobe (ATL).…”
mentioning
confidence: 65%
“…This lends support to the hypothesis that domain-general executive processes interact with semantic representations to support controlled aspects of semantic cognition, and provides further evidence for the proposal that SA cases have a semantic deficit that reflects poor control over conceptual retrieval. While there are some regions implicated in semantic and not domain-general executive control, such as pMTG and anterior ventral IFG (e.g., Badre et al, 2005;Davey, Cornelissen, et al, 2015, 2016Humphreys & Lambon Ralph, 2015;Noonan et al, 2013), controlled semantic processing is supported by multidemand as well as semantic regions (Humphreys & Lambon Ralph, 2015;Noonan et al, 2013;Whitney et al, 2012). Indeed, although the function of these regions appears to be at least partially distinct, recent network (path) analyses of whitematter DTI and resting-state fMRI data indicate that they form a 'single functional module' arising from their physical white-matter connections (Jung, Cloutman, Binney, & Lambon Ralph, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…SA patients have left‐hemisphere damage focused on inferior frontal gyrus (IFG) and posterior middle temporal gyrus (pMTG) (Gardner et al ., ; Noonan, Jefferies, Corbett, & Lambon Ralph, ; Thompson, Robson, Lambon Ralph, & Jefferies, ), and deficits affecting the comprehension of words, objects, environmental sounds, and actions (Corbett, Jefferies, Ehsan, et al ., ; Corbett, Jefferies, & Lambon Ralph, , ; Gardner et al ., ; Jefferies & Lambon Ralph, ). Similar brain regions have been implicated in the control of semantic processing by neuroimaging and neurostimulation studies (Badre, Poldrack, Paré‐Blagoev, Insler, & Wagner, ; Davey, Cornelissen, et al ., ; Davey, Rueschemeyer, et al ., ; Davey, Thompson, et al ., ; Krieger‐Redwood, Teige, Davey, Hymers, & Jefferies, ; Noonan et al ., ; Thompson‐Schill, D'Esposito, Aguirre, & Farah, ; Whitney, Kirk, O'Sullivan, Lambon Ralph, & Jefferies, ). These regions include dorsal and posterior IFG and inferior frontal sulcus (IFS) within the multidemand executive network (Duncan, ; Humphreys & Lambon Ralph, ) – that is, regions implicated in executive control across different domains and not just semantic tasks – as well as anterior IFG and pMTG more specifically implicated in semantic control.…”
Section: Introductionmentioning
confidence: 99%
“…The posterior MTG plays a key role semantic control processes (Binder & Desai, 2011; Davey et al, 2015; Davey et al, 2016; Noonan, Jefferies, Visser, & Lambon Ralph, 2013; Price, 2010) and is commonly implicated in studies of creativity (Gonen-Yaacovi et al, 2013; Shen et al, 2017). Recently, Davey et al (2016) investigated the functional role of the left posterior MTG in semantic control, and showed that the left posterior MTG integrates information from the DMN and ECN.…”
Section: Discussionmentioning
confidence: 99%